Balkan Archaeology as a Laboratory: Challenging old paradigms and experimenting with new ones - Gori, Maja; Heilmann, Daniela; Penezić, Kristina (Ex Novo: Journal of Archaeology, 2024)
In archaeology, paradigms not only shape our understanding of the past but also reflect the socio-political contexts in which they are developed and applied. Paradigms in archaeology are dynamic entities, shaped and reshaped by socio-cultural, political, and intellectual contexts.